PEREMPUAN DALAM PERSPEKTIF KEBUDAYAAN - Asmarani, Ratna (Sabda: Jurnal Kajian Kebudayaan, 2017)
This paper aims to analyze women from a cultural perspective based on R.A. Kartiniâ€™s thoughts and struggles. The focus of the study is on R.A. Kartiniâ€™s thoughts and struggles concerning the custom of â€œpingitanâ€ (seclusion), non-schooling culture, and polygamy culture closely related to the life of Javanese noble women. This paper also analyzes the perspective underlying the thinking and struggle of R.A. Kartini. The last discussion critically analyzes R.A. Kartiniâ€™s thoughts and struggles to devise a study of feminism that touches the root of Indonesian culture which would be very appropriate to study women's problems in local culture. The result of the study shows that the thinking and struggle of R.A. Kartini are sharpened and hegemonized by Western thinking about emancipation and equality when criticizing the existence of Javanese noble women in the custom of seclusion, non-schooling culture, and polygamy culture.